PENGARUH QUALITY OF WORK LIFE DAN PENGEMBANGAN KARIER DENGAN MODERASI KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI ( Studi Pada Pegawai Dinas Perhubungan Komunikasi dan Informatika Kabupaten Rembang ) - Pribowo, Arief; Tjahjaningsih, Endang (Jurnal Ilmiah Telaah Manajemen, 2015)
This research investigates and examines the Effect of Quality of Work Life and Carrier development on Employees performance by using Organizational commitment as moderating role in Comunication Transportation and Information Rembang. This research uses cencus sampling method. The collected sample is 105 respondent. The instrument testing used validity and reliability by alpha cronbach value. Model measurement uses Coefficient determination and F testing. Hypotheses testing uses multiple linier Regression and t testing. The result found that Quality of Work Life ( QWL ) positively and significantly effects the employees performance, Career development positively and significantly affectsthe employees performance which moderated by organizational commitment and Career Development has positive and significant effect on employees performance which is moderated by organizational commitment in Communication Transportation and Information of Rembang. Keywords : Quality of Work Life ( QWL ) , Career development, Organizational Commitment and Employees Performance.